2020
DOI: 10.3390/rs12203434
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Crop and Grass Productivity over the United States Using Satellite Solar-Induced Chlorophyll Fluorescence, Precipitation and Soil Moisture Data

Abstract: This study investigates how gross primary production (GPP) estimates can be improved with the use of solar-induced chlorophyll fluorescence (SIF) based on the interdependence between SIF, precipitation, soil moisture and GPP itself. We have used multi-year datasets from Global Ozone Monitoring Experiment-2 (GOME-2), Tropical Rainfall Measuring Mission (TRMM), European Space Agency Climate Change Initiative Soil Moisture (ESA CCI SM), and FLUXNET observations from ten stations in the continental United States. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…Water availability in the early phases of plant development affects the final product (Zargar et al, 2017). Climate change impacts maize growth via altered rainfall patterns and rising temperatures (Halubok and Yang, 2020). Over 35 o C is Optimum for maize development at every stage from fertilization to grain filling (Adam, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Water availability in the early phases of plant development affects the final product (Zargar et al, 2017). Climate change impacts maize growth via altered rainfall patterns and rising temperatures (Halubok and Yang, 2020). Over 35 o C is Optimum for maize development at every stage from fertilization to grain filling (Adam, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Water availability in the early phases of plant development affects the final product (Zargar et al, 2017). Climate change impacts maize growth via altered rainfall patterns and rising temperatures (Halubok and Yang, 2020). Over 35 o C is Optimum for maize development at every stage from fertilization to grain filling (Adam, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… Rojas et al (2019) , for example, by analyzing both the annual mean precipitation and specific growing seasons and areas found that reduced precipitation will impact, before 2040, maize production in southern Africa and Europe. Considering that the variability of precipitation is an essential factor because water availability during a given stage of plant developmental influences plant production at later stages of the life cycle ( Brouwer and Heibloem, 1986 ; Kranz et al, 2008 ; Al-Kaisi and Broner, 2009 ; Hashim et al, 2012 ; Halubok and Yang, 2020 ), it is likely that more regions of the globe with maize crops will be concerned. In addition, in the context of climate change, not only changes in rainfall patterns affect maize growth, but also increases in temperature.…”
Section: Introductionmentioning
confidence: 99%